Madhuca kanchanaburiensis (Sapotaceae), a new species from Thailand - Chantaranothai, Pranom; Kunasit, Pongsakorn; Kladwong, Pornchai (Phytotaxa, 2022)
A new species of Madhuca from Thailand, M. kanchanaburiensis is described and illustrated. The species appears most similar to M. malaccensis and M. punctata, but differs in having conspicuous secondary veins toward the leaf margin, woolly filaments and longer corolla. The vernacular name and conservational status of this endemic species are also provided.